Spatial Justice and Accessibility: Optimizing Sports Facility Allocation in Tehran - Rohollah Asgari Gandomani; Amir Rahimi; Leila Shahbazpour; Jamal Jokar Arsanjani (Land, 2025)
The optimal allocation of sport facilities is crucial for urban management, as it enhances public health and improves citizens’ quality of life. This study proposed a novel decision-making approach for optimizing the allocation of sports facilities in a megacity in which accessibility to sports facilities is a major challenge. To achieve this, 23 criteria in three categories of compatibility, environmental, and infrastructural criteria were analyzed. The analytical hierarchy process (AHP) method determined the criterion weights, while the weighted linear combination (WLC) method integrated them. The results showed that the current spatial distribution of sports facilities in Tehran follows a clustered pattern, and the compatibility criterion, with a weight of 0.45, has the greatest impact on the sports facility location selection process. A spatial analysis identified 48.58 km2 as being highly suitable for facility development, mainly in central and southern Tehran. These findings can assist urban managers and planners in improving spatial justice, increasing accessibility to sports facilities, and promoting sustainable urban development.